AN ANALYSIS OF GENERIC STRUCTURE ON RECOUNT TEXT WRITTEN BY ACCELERATED STUDENTS AT SMAN 1 PRAYA TENGAH IN ACADEMIC YEAR 2021/2022 - Baiq Wilda Muliadi; Sahuddin; Udin (Journal of English Education Forum (JEEF), 2022)
This study attempted to find out how the generic structure on recount text is written by accelerated students at SMAN 1 Praya Tengah in academic year 2021/2022. The method applied was the qualitative technique. The population of the research was accelerated students at SMAN 1 Praya Tengah with the samples as many as 20 students. Many students wrote recount texts appropriately based on the generic structure required but others still needed to learn more. The class mean score of the students' test results is 22.9 while the highest and lowest scores from 20 students in an accelerated class are 28 and 12 respectively. The students' test results in each generic structure have been calculated and it shows that the orientation is 8.9, series of events 7.5, and re-orientation 6.5. The highest and lowest percentages of all are 38.86% and 28.38%. As a result, the students understand orientation better than a succession of events and re-orientation.